Optimalisasi Deskripsi Produk E-commerce: Manfaatkan AI ChatGPT untuk Deskripsi Menarik & Kontekstual - Firdo, Daud; Kristianto, Hefi; Pranatawijaya, Viktor Handrianus; Sari, Nova Noor Kamala (Universitas Multi Data Palembang, 2024)
This research aims to optimize the process of creating product descriptions for E-commerce automatically using artificial intelligence-based ChatGPT. The method used is by providing input in the form of product names and specifications into the ChatGPT model then the model will generate product descriptions automatically. Implementation is done using ChatGPT API and JavaScript programming language. As a result, the ChatGPT model is able to generate relevant and varied product descriptions based on the input given. However, this research has not considered the evaluation of the quality and accuracy of the description in depth. Further research needs to be conducted to improve the performance of the ChatGPT model in generating product descriptions.